2012
DOI: 10.3109/07420528.2012.728654
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Effect on Infants' Sleep Regulation: A Preliminary Study in a Mediterranean Climate

Abstract: Infants' sleep-wake rhythms are influenced by multiple factors, including developmental and contextual aspects, as well as circadian cycles. Empirical studies that address the seasonal impact on infants' sleep are scarce. The present study examined aspects of sleep schedule and quality, comparing summer and winter months in a Mediterranean climate. This report is based on a convenience sample of 34 healthy 7-mo-olds, an age in which sleep is well consolidated and regulated compared with the first few months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…To date, evidence suggests that the seasonal effect increases the time spent in bed and the sleep length during winter (O'Connell et al 2014;Paul et al 2015). In children, summer is found to provoke more restless sleep and active sleep at the expense of quiet sleep (Aronen et al 2002;Cohen et al 2012). However, to the best of our knowledge, there is a scarcity of evidence regarding the seasonal effects on the sleep quality and architecture of infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, evidence suggests that the seasonal effect increases the time spent in bed and the sleep length during winter (O'Connell et al 2014;Paul et al 2015). In children, summer is found to provoke more restless sleep and active sleep at the expense of quiet sleep (Aronen et al 2002;Cohen et al 2012). However, to the best of our knowledge, there is a scarcity of evidence regarding the seasonal effects on the sleep quality and architecture of infants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent review demonstrated that adults have lower subjective sleep quality, more sleep fragmentation, and less deep sleep during the Antarctic winter (Pattyn et al 2018). Conversely, an abundance of REM/R or active sleep has been observed in adults during the summer months in the Antarctic and in an actigraphy study of 7-month-old infants in Mediterranean countries (Cohen et al 2012;Pattyn et al 2017). Data from one questionnairebased study reported that infants born in spring sleep for the longest during the night (Iwata et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Daylight length variation has been suggested as one of the variables that may affect seasonal differences in growth [ 20 ]. Wake and sleep times, both important for early childhood development [ 53 ], are also influenced by sunlight [ 54 ]. A study conducted in Israel found seasonal effect on infant sleep regulation: in the summer months, sleep onset occurred at a later hour and more motor activity during sleep was detected, compared to winter [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wake and sleep times, both important for early childhood development [ 53 ], are also influenced by sunlight [ 54 ]. A study conducted in Israel found seasonal effect on infant sleep regulation: in the summer months, sleep onset occurred at a later hour and more motor activity during sleep was detected, compared to winter [ 53 ]. In poor rural Qinba mountainous area, there is a significant gap in the sunshine duration between summer and winter.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this finding, a study of 5‐ to 12‐year‐old Finnish children showed less actigraphy‐measured activity during the darker months (Aronen, Fjallberg, Paavonen, & Soininen, 2002). A study of 34 infants aged 7 months did not show seasonal differences in sleep length or the number of awakenings (Cohen, Atun‐einy, & Scher, 2012). However, this could be due to lack of power or less variation in day length as the study was carried out in Israel.…”
Section: Discussionmentioning
confidence: 99%